PROFIL PASIEN DIABETES MELITUS TIPE 2 RAWAT INAP DI SATU RS X: STUDI DOKUMENTASI [PROFILE OF TYPE 2 DIABETES MELLITUS PATIENTS HOSPITALIZED IN HOSPITAL X: A DOCUMENTATION STUDY] - Saununu, Angel T. I; Lenggu, Erland N; Ndaparoka, Kacie R. G; Juhdeliena, Juhdeliena; Yulia, Yulia (Nursing Current: Jurnal Keperawatan, 2024)
Complications in patients with type 2 diabetes mellitus can increase the number of hospitalizations and even worsen the patient's condition even to death if not handled properly. Based on data from type 2 DM patients who underwent hospitalization at Hospital X in October-November 2021, 145 patients increased to 192 patients the following year. The purpose of this study is to identify the profile of patients hospitalized with type 2 diabetes. This research employed a quantitative descriptive study with a retrospective approach. The instrument in this study used a fill-in sheet. A total of 141 medical record records were included in the sample. The data were analysed using univariate analysis. The findings indicated that the majority of hospitalized patients with type 2 DM presented with complaints of weakness, accounting for 42.55% of cases. Patients with hyperglycaemic conditions were predominantly in the pre-elderly age category, comprising 24.10% of cases, with a higher representation of females at 27.7%. Additionally, a significant proportion of patients had a normal body mass index (17%), while a considerable number did not have their HbA1c levels checked (26.20%). Furthermore, 22.7% of patients had uncontrolled HbA1c levels (>7%), and 35.50% had one to three comorbidities. Several factors require additional investigation, specifically the hormonal history and gestational diabetes in women. Furthermore, there is a need for further research on visceral fat in the body, stress levels in hospitalized Type 2 DM patients, and the types of comorbid diseases commonly found in Type 2 DM patients. Additionally, routine HbA1c checks are necessary.BAHASA INDONESIA Komplikasi pada pasien diabetes melitus (DM) tipe 2 dapat meningkatkan peningkatan angka rawat inap bahkan dapat memperburuk kondisi penderita bahkan sampai dengan kematian jika tidak ditangani dengan baik. Berdasarkan data rawat inap pasienDMtipe2di satu RS X pada bulan Oktober-November 2021 sebanyak 145 pasien  meningkat menjadi 192 pasien ditahun berikutnya. Tujuan penelitian ini untuk mengidentifikasikarakteristik pasien DMtipe2 yang menjalani rawat inap. Metode penelitian ini deskriptif kuantitatif dengan pendekatan retrospektif. Instrumen dalam penelitian ini menggunakan lembar isian. Sampel yang digunakan berjumlah 141 dokumen rekam medis. Teknik analisis data yaitu analisis univariat. Hasil menunjukkan bahwakarakteristik pasien DM tipe 2 rawatinap mayoritas datang dengan keluhan lemas sebanyak 42,55%, pasien dengan kondisi hiperglikemi mayoritas dalam kategori usia pra lanjut usia sebanyak 24,10%, dengan jenis kelamin perempuansebanyak 27,7%,indeks massa tubuh normal sebanyak 17%,Kadar HbA1c tidak diperiksa sebanyak 26,20%, dan dengan kondisi kadar HbA1c tidak terkendali (>7%) sebanyak 22,7%, serta memiliki satu sampai tiga komorbid sebanyak 35,50%. Ada banyak faktor yang perlu dilakukan penelitian lebih lanjut yaitu riwayat hormonal dan diabetes gestasional pada perempuan, selain itu diperlukan penelitian lebih lanjut terkait lemak viseral dalam tubuh, tingkat stres pada pasien rawat inap DM Tipe 2 dan jenis-jenis penyakit komorbid yang sering terjadi pasien DM Tipe 2, dilanjutkan dengan diperlukannya pemeriksaan rutin HbA1c.